2017
DOI: 10.1097/aud.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Performance and Electrical Stimulation Measures in Cochlear Implant Recipients With Auditory Neuropathy Compared With Severe to Profound Sensorineural Hearing Loss

Abstract: Prelingual children with isolated AN who fail to show expected oral and auditory progress after extensive rehabilitation with conventional hearing aids should be considered for cochlear implantation. Children with isolated AN had similar pattern as children with SNHL on auditory performance tests after cochlear implantation. The lower current charge required to evoke subjective and objective electrical thresholds in children with AN compared with children with SNHL may be attributed to the contribution to elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
1
25
0
8
Order By: Relevance
“…The hearing evaluation through the BAEP showed that most of the infants had a high electrophysiological threshold, but that this change was transient in 38% of the findings obtained on the right ear and in 42% of the ones obtained on the left ear and we emphasize that the middle ear changes were excluded by the ENT doctor and tympanometry. These thresholds recovery were also reported by other authors when they reported that the absence of response in the audiological evaluation does not represent a permanent hearing loss, since many factors may compromise the maturation of the auditory pathways or the ability to respond to a certain auditory threshold [18][19][20].What should also be considered is that the third trimester of gestation is extremely important for the auditory system maturation, since in this period of the cochlear myelinization begins between the cochlea and the brainstem [18,19,21]. Consequently, premature infants could have BAEP abnormal, however the changes observed in our study were in full-term and premature infants, regardless of gestational age.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The hearing evaluation through the BAEP showed that most of the infants had a high electrophysiological threshold, but that this change was transient in 38% of the findings obtained on the right ear and in 42% of the ones obtained on the left ear and we emphasize that the middle ear changes were excluded by the ENT doctor and tympanometry. These thresholds recovery were also reported by other authors when they reported that the absence of response in the audiological evaluation does not represent a permanent hearing loss, since many factors may compromise the maturation of the auditory pathways or the ability to respond to a certain auditory threshold [18][19][20].What should also be considered is that the third trimester of gestation is extremely important for the auditory system maturation, since in this period of the cochlear myelinization begins between the cochlea and the brainstem [18,19,21]. Consequently, premature infants could have BAEP abnormal, however the changes observed in our study were in full-term and premature infants, regardless of gestational age.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the electrophysiological record of the auditory function, both in latency and threshold research, is characterized by evolutionary parameters that must be taken into account during the analysis [22,23]. Another aspect to be highlighted concerns the clinical history of the infant, since neonates with risk indicators are frequently referred for auditory evaluation and studies show reversibility in BAEP findings in cases of hyperbilirubinemia with transfusion levels, or in those auditory neuropathy [21,22,24]. However, there were no infants with these characteristics, but who showed changes between the exams.…”
Section: Discussionmentioning
confidence: 99%
“…For SNHL, management is typically driven by the severity of the hearing loss with amplification by hearing aids in individuals with mild to moderate SNHL, and cochlear implantation in individuals with a severe or profound auditory threshold, provided that the anatomy of the inner ear appears favorable. However, it has been suggested that cochlear implants be considered in individuals with AN, who often fail to gain benefit from conventional hearing aids, 24 with several reports of successful cochlear implantation outcomes in AN patients with an OTOF -related cause. 25 , 26 This being the case, early detection of AN may be critical to maximize the verbal and cognitive benefits of cochlear implantation at an earlier age.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 This being the case, early detection of AN may be critical to maximize the verbal and cognitive benefits of cochlear implantation at an earlier age. 24 Currently, newborn screening in Saudi Arabia relies on OAE testing, which will often appear as normal in infants with OTOF -related hearing loss. The enrichment of OTOF variants in this cohort makes a strong case for mandatory auditory brain response testing as part of newborn screening programs in Saudi Arabia, as well as neighboring countries with populations having common tribal ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…işitsel nöropatili bireylerde objektif nöral yanıt elde etmek için daha düşük akım seviyesine ihtiyaç duyulduğunu göstermişlerdir. 21,23 İşitsel nöropatinin heterojen yapısı ve henüz bilinmeyen birçok yönünün olması, durumu açıklamayı zorlaştırmaktadır. İşitsel nöropatili kulaklarda preoperatif rezidüel tüy hücreleri ve nöral yapıların daha büyük miktarlarda olması spiral ganglionlardan önce tüy hücrelerinde uyarıma sebep olmaktadır.…”
Section: Konuşma İşlemci̇si̇ Kullanim Süreleri̇unclassified